Innovation of Indonesian School Book Publishing Companies in Response to Digital Transformation - Zaenah, Eny Rahma; Susilowati, Indah; Iskandar, Deden Dinar; Kartono, Drajat Tri (Journal of Ecohumanism, 2024)
This study aims to determine the digital transformation of education in Indonesia and how PT Tiga Serangkai, a school book publishing company, innovates as an adaptive attitude to the transformation. Researchers used a mixed convergent parallel design approach. The study population included primary and secondary schools in Central Java Province that used Tiga Serangkai products. Researchers obtained 119 schools as a sample with a confidence level of 90%. Data collection using questionnaires to determine the determinants of innovation acceptance and interviews with selected resource persons. Qualitative data were obtained through literature studies, focus group discussions, and in-depth interviews with selected resource persons (purposive sampling). The results showed that there is a digital transformation in education in Indonesia in the form of changes in learning media, procurement systems, and the amount of budget. PT Tiga Serangkai responds with innovations in production, distribution and consumption patterns, and products. This article reveals the digital transformation in the scope of education that occurs in Indonesia. The research findings show PT Tiga Serangkai’s book publishing adaptability through product innovation. This article contributes to the literature on adapting schoolbook publishing companies to digital transformation. Not only digitizing products in the form of e-books but also complementing with supporting facilities that provide convenience, comfort, and completeness for schools which are the primary target consumers of their products.